PERANCANGAN SISTEM INFORMASI MANAJEMEN ORDER DISTRIBUSI PAKET BERBASIS WEBSITE PADA PT. CAKRAWALA NUSANTARA EXPRESS - Usanto Usanto; Septiana Ningtyas; Resha Syafira (JRIS : Jurnal Rekayasa Informasi Swadharma, 2021)
The rapid development of computer technology provides convenience, speed and accuracy in accessing and processing information, so that the use of computers can assist humans in carrying out work, especially to present information quickly, accurately, without taking up a lot of time and effort. PT. Cakrawala Nusantara Express is a company engaged in motorized transportation for general goods. Currently, the delivery system is still using the manual method with Microsoft Excel to distribute goods shipments. Where in recording company data, recording orders, searching data, knowing the status of shipments, there are still many errors. Therefore, a web-based delivery application was made. Based on the above problems, PT. Cakrawala Nusantara Express requires a goods distribution information system that is able to simplify the package delivery process. It is hoped that with this goods distribution information system, PT. Cakrawala Nusantara Express can operate optimally